Analysis of a supply chain under advance demand information - Eş, Emine. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
In this study we investigate the effects of incorporating advance demand information in a two-echelon distribution model which consists of a central depot and several retailers. The depot is not allowed to hold inventory. In particular, the benefits of advance demand information on system costs and ordering and allocating policies are investigated. Two types of advance demand information structures are considered. Under perfect and partial advance demand information structures, the approximate optimal ordering and allocating policies and the expected system cost are obtained. A computational study is presented in order to demonstrate the effect of system parameter.
Keywords: Business logistics.; Industrial procurement.